Initial teacher training. New formula to combat new educational challenges - Callealta Oña, Leopoldo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The current educational systems have as a consensus the idea of creating organizations capable of responding to the new paradigms that arise from political changes and European transformations in relation to Quality and the responsibility to train future applicants in teaching. The main objective is to analyze the influence of current educational challenges on initial teacher training and to systematize the evidence that such training reflects in order to combat the new changes. It is a bibliographic-documentary work, demonstrating the reflection of the importance that initial training has gained in the face of persistent educational changes over time, exhibiting once again the value of such training in the teaching-learning processes.